Balancing Freedom Of Information And Social Responsibility In The Democratic Development Of Uzbekistan (Open Herald: Periodical of Methodical Research, 2026)
In the era of rapid digital transformation, balancing the freedom of information with social and ethical responsibility stands as a critical challenge for emerging democracies. This study explores the evolutionary trajectory and structural elements of information freedom within the context of democratic reforms and civil society building in New Uzbekistan.